Another construction of edge-regular graphs with regular cliques - Greaves, Gary Royden Watson (2020)
We exhibit a new construction of edge-regular graphs with regular cliques that are not strongly regular. The infinite family of graphs resulting from this construction includes an edge-regular graph with parameters (24,8,2). We also show that edge-regular graphs with 1-regular cliques that are not strongly regular must have at least 24 vertices.